2019
DOI: 10.30969/acsa.v14i4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia do coqueiro anão verde em região semiárida

Abstract: A fenologia pode ser definida como o estudo dos eventos periódicos da vida da planta em função da sua reação às condições do ambiente, e sua importância está relacionada ao manejo que pode ser desenvolvido para as culturas em função desses resultados. Com o objetivo de avaliar a fenologia do coqueiro, um experimento foi conduzido no pomar didático da Universidade Federal Rural do Semi-Árido-UFERSA. A área experimental foi composta por coqueiros da variedade anão verde com quatro anos de idade, propagadas via s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…3) constitutes a good vegetative aspect of coconut trees, besides being above the values found in the literature, once, according to Castro et al (2009), when environmental conditions favor the canopy development, the coconut tree may reach between 25 and 30 leaves, and the authors observed between 18 and 27 live leaves. Ferreira Neto et al ( 2007) and Câmara et al (2019) in studies with coconut trees in the Northeast region accounted for an average of 22.25 and 22.28 leaves, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3) constitutes a good vegetative aspect of coconut trees, besides being above the values found in the literature, once, according to Castro et al (2009), when environmental conditions favor the canopy development, the coconut tree may reach between 25 and 30 leaves, and the authors observed between 18 and 27 live leaves. Ferreira Neto et al ( 2007) and Câmara et al (2019) in studies with coconut trees in the Northeast region accounted for an average of 22.25 and 22.28 leaves, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Under water deficit, the coconut palm reduces the growth and the number of flowers (Silva et al 2017). Also, a decrease in the fruit size, as well as the abortion of fruits, may happen, which results in low yield (Araújo et al 2022, Câmara et al 2019). Thus, irrigation has been used as management practice to minimize these effects and allow the expansion of its cultivation in regions with seasonal water deficit (Santos et al 2020) when water demand is not met by rain events.…”
Section: Introductionmentioning
confidence: 99%
“…Other, equally important, factors involve vegetative and reproductive aspects, such as the age of the coconut palm trees and climatic conditions, particularly in semi-arid regions where there is an uneven distribution of rainfall, leading to the atrophy of bunches of fruits in dry periods (CÂMARA et al, 2019). In established plantations, the accumulation of residual organic matter from coconut palm trees, and other organic residues may signifi cantly affect the rhizospheric soil microbiota (MALHOTRA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%